Peterson's ACT prep guide 36 : (Peterson's, 2016)
Peterson’s ACT® Prep Guide 36 is an advanced test prep resource for competitive students who want to maximize their already good ACT test scores. This guide also preps first-time test takers who know the basic concepts, consider standard practice questions in other guides too easy, and plan to score high on their initial ACT test.